2014
DOI: 10.3311/ppch.7300
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surfactants to the stability of coal water suspension

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…After substituting the approximation function into the analytical solution and integrating over the approximation time, a sufficient identification accuracy of 0.018% was determined. The dependences revealed in the study [7] are confirmed by other authors [8][9][10][11]. For example, in the research [11] the influence of substances included in the composition of the fuel on the ignition of coal-water fuel was shown [12][13][14][15].…”
Section: Problems Of Research Of Methods For Solving Boundary Value Nsupporting
confidence: 82%
See 1 more Smart Citation
“…After substituting the approximation function into the analytical solution and integrating over the approximation time, a sufficient identification accuracy of 0.018% was determined. The dependences revealed in the study [7] are confirmed by other authors [8][9][10][11]. For example, in the research [11] the influence of substances included in the composition of the fuel on the ignition of coal-water fuel was shown [12][13][14][15].…”
Section: Problems Of Research Of Methods For Solving Boundary Value Nsupporting
confidence: 82%
“…Therefore, simplifying the reduction to a single-layer model requires estimates of discontinuous physical properties and is modeled by Heaviside asymmetric unit functions. There are known applications of this method for modeling the first stage of unsteady heat conduction, in particular, for the combustion process [6][7][8][9][10][11]. After substituting the approximation function into the analytical solution and integrating over the approximation time, a sufficient identification accuracy of 0.018% was determined.…”
Section: Problems Of Research Of Methods For Solving Boundary Value Nmentioning
confidence: 99%
“…Surfactants adsorption at a solution/solid interface is very important phenomenon in many colloid-chemical processes, including flotation of ores, oil recovery, foam forming, detergency, stabilization of the colloids, emulsification, chemical synthesis and water treatment. In many cases the surfactants mixtures are more beneficial than the single surfactants [1][2][3][4]. The use of surfactant mixtures allows to more effectively affect the properties of dispersed systems than the individual components.…”
Section: Introductionmentioning
confidence: 99%